Optimalisasi Penerimaan Laba Badan Usaha Milik Negara Sektor Perbankan Sebagai Upaya Meningkatkan PNBP - Martha Carolina (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2020)
This study aims to analyze the reasons for the inadequate income of state-owned enterprises (BUMN) in the banking sector and the government's efforts to strengthen these enterprises to increase Non-Tax State Revenues (PNBP). This research is descriptive quantitative research. The study results show that state-owned enterprises in the banking sector need to improve financial performance to increase the PNBP of Separated State Assets (KND). The results showed that this study had passed the classic assumption test. The F test shows that the independent variables simultaneously affect the dependent variable with a significant value of 0.000. The study shows that return on assets/ROA (X1) affects DPR (Y), and ROA has a positive effect on DPR. While the variable capital adequacy ratio/CAR (X2) affects the DPR (Y). CAR has a positive effect on DPR. Realization of PNBP KND in 2017/2018, 2018/2019, and 2019/2020 always exceeded the target of Non-Tax State Revenues of Separated State Assets (PNBP KND).